B2B business strategies of freight forwarding industries in Bangladesh and their operation: an in depth study of KUEHNE + NAGEL Bangladesh Ltd. - Ansary, Khaled Saifullah (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.